Coordination Properties of Klaeui's Tripodal Oxygen Donor toward Zirconium(IV) - Ward, Thomas R.; Duclos, Severine; Therrien, Bruno; Schenk, Kurt (My University, 1998)
The coordination properties of [(?5-C5H5)Co{PR2(O)}3]- (R = OEt (LOEt-), Et (LEt-)) toward Zr(IV) were studied and compared to related cyclopentadienyl complexes. Addn. of 2 equiv of LOEt- to [ZrCl4(THF)2] yields labile [Zr(LOEt)2Cl2] (2), which undergoes Arbuzov dealkylation to yield a dinuclear, seven-coordinate complex 1 (shown as I, R = OEt). Reaction of 2 with MeLi yields the metathesis product LiLOEt. Addn. of 2 equiv of AgOTos to 2 affords octahedral [Zr(LOEt)2](OTos)2 (3). Reaction of [ZrCpCl3] with LOEt- leads to Cp- displacement to give [ZrLOEtCl3] (4). Addn. of 2 equiv of LEt- to [ZrCl4(THF)2] yields octahedral [Zr(LEt)2](Cl)2 (5). Compds. 1, 3, 4, and 5 were characterized by x-ray crystallog. [on SciFinder(R)]
Keywords: crystal structure zirconium cobalt cyclopentadienyl phosphinyl; mol structure zirconium cobalt cyclopentadienyl phosphinyl; Arbuzov dealkylation alkoxyphosphinyl cobalt cyclopentadienyl zirconium; zirconium cobalt cyclopentadienyl phosphinyl prepn structure